Remarkable lives: Charlotte Tetley in conversation with Jerome Carson. Issue 3 (10th August 2015) - Tetley, Charlotte; Carson, Jerome
Abstract : Purpose: – The purpose of this paper is to provide a profile of Charlotte Tetley. Design/methodology/approach: – Charlotte provides a short biographical account and is then interviewed by Jerome. In the biography Charlotte talks about her long battle with mental health problems and treatments that did not help. Findings: – Charlotte's mental health problems started at the age of 12 and eased when she left home at 17. It was in her final year at university that her problems returned. Research limitations/implications: – Charlotte's story is one of not just surviving long term mental health problems, but of coping with adversity and becoming a stronger person. It is one of thousands of remarkable survivor accounts. Practical implications: – The story of the involvement of local police officers in Charlotte's admission to hospital, is once more a sad indictment of the brutality handed out to many sufferers in acute mental distress. Social implications: – Considering her background, 12 different schools, two exclusions, childhood mental health problems, Charlotte's story shows the triumph of the human mind against social disadvantage. She is "somebody who conquered the storm". Originality/value: – Charlotte was helped by her indomitable spirit, by her mother, a therapist and a friend who stood by her. She tells us she can never be the same person she was before her mental health problems, but she has grown and in the process became a stronger person.